2012
DOI: 10.1007/s12639-012-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical anaplasmosis in camel (Camelus dromedarius) and its successful therapeutic management

Abstract: On the Indian sub continent, dromedarian camel -'the ship of the desert' is an important constituent of the socio economic life style of nomadic owners in the semi arid to arid ecosystems. The animal suffers from a few parasitic diseases viz. surra, coccidiosis, sarcocystis, gastro intestinal concurrent metazoan infections, mange, nasal bots and ticks infestations. However, anaplasmosis in camel has not been reported so far from the Indian subcontinent. Systematic investigations of a 7 year male Jaisalmeri cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 3 publications
(2 reference statements)
1
15
1
Order By: Relevance
“…Regarding anaplasmosis, there is such dearth of research on camel anaplasmosis. A. marginale is considered capable of infecting dromedaries [51], and the occurrence of subclinical anaplasmosis was addressed in dromedaries' camels [52]. In the present study, 47.4% of examined camels were harbored anaplasmosis by GSBS, while the overall infection rate recorded by PCR was 67.4% (223/331), of them, 78.9% and 63.1% were found in males and females, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…Regarding anaplasmosis, there is such dearth of research on camel anaplasmosis. A. marginale is considered capable of infecting dromedaries [51], and the occurrence of subclinical anaplasmosis was addressed in dromedaries' camels [52]. In the present study, 47.4% of examined camels were harbored anaplasmosis by GSBS, while the overall infection rate recorded by PCR was 67.4% (223/331), of them, 78.9% and 63.1% were found in males and females, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…From the genus Anaplasma to date Anaplasma phagocytophilum, A. platys, A. ovis and A. capra have been recognized to infect humans [2][3][4][5]. In camels Anaplasma organisms have been reported in blood smears by light microscopy [6,7] and antibodies against them in blood serum [8,9]. However, so far the only Anaplasma species Anaplasmataceae, spotted fever group (SFG) rickettsiae, Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reviews the current knowledge on camels' tickborne bacteria including microscopy, serology and molecular studies.confirmed by DNA sequencing in camels are Candidatus Anaplasma camelii (genetically close to A. platys), A. phagocytophilum and A. ovis [10][11][12][13][14][15][16][17][18]. Clinical signs of natural infections are described as fever, pale and icteric conjunctiva suggestive of anaemia, dullness, anorexia, diarrhoea, loss of appetite, emaciation, coughing, lacrimation, rough hair coat, abortion, and/or infertility [7,19]. Intramuscular administration of oxytetracycline at 20 mg/kg as specific therapy and injectable B-complex, iron, folic acid and hydroxycobalamin as supportive therapy is the recommended therapeutic regimen [7,19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In camels, recent studies reported the presence of Anaplasma and Ehrlichia spp. (Sudan et al 2014;Bastos et al 2015). Although decision for treatment can be based on clinical signs and symptoms, yet microscopic examination of Giemsa-stained thin peripheral blood smears was used to demonstrate cytoplasmic morula for diagnosis of ehrlichiosis and anaplasmosis.…”
Section: Introductionmentioning
confidence: 99%